Językowy obraz kobiety w prasie dla pań (na przykładzie „Zwierciadła”, „Przyjaciółki” i „Cosmopolitan”) - Spychała-Reiss, Magdalena (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2009)
The article presents a linguistic picture of a woman shown in the contemporary women’s magazines. The material studied has been derived from three women’s magazines: Zwierciadło, Cosmopolitan and Przyjaciółka (specifically, from the issues published between December 2006 and February 2008). It has been limited to the lexeme woman; all its synonyms and paraphrases have been disregarded. In the material discussed, this word shows semantic relationships with a repetitive number of subjects. On the basis of observations the author has prepared a list of 12 profiles, which, in turn, got divided into subcategories—facets. The excerpts thus classified and grouped have revealed the fact that a linguistic picture of a woman differs, to some extent, in each of the studied periodicals, depending on the character of the magazine. Woman readers, while identifying themselves with this picture, form exclusive communicative and social communities. Parallely, a linguistic picture of a woman in each of the magazines is not homogenous since it refers to different women. It contains all the attributes of the subject , both the “sufficient” ones (identifying the defined meaning with similar meanings) and the “indispensible” ones (differentiating the lexeme described from the rest of the world) as well as the “typical” ones, relevant from the point of view of the usage of the word in linguistic texts and its relation to other linguistic items.